Engineering properties of concrete coarsely crushed cockle shell as coarse aggregate replacement - Teh, Gek Yu (2013)
Various studies had been carried out by using waste products to replace the current material use for concrete. One of the wastes that can be obtained from aquaculture industry is cockle shell. It had been found out that cockle shell has the potential to replace coarse aggregate. This research presents the result on the engineering properties of coarsely crushed cockle shell as coarse aggregate replacement in concrete. Two mix proportions are used throughout this research which are 1:1.8:0.7 and 1:1:1.5 which is consist of cement to sand to aggregateo All samples were prepared with constant cement content of 500kg/m3 and w/c ratio of 0.4. Samples are subjected to water curing for 3, 7 and 28 days. The mix proportion of 1: 1: 1.5 obtained better result in terms of workability, compressive strength, flexural strength and modulus of elasticity. The effect of cockle shell towards fresh concrete will reduce the workability. Cockle shell in concrete will lowered the strength but differences are insignificant. Conclusively, the results revealed that the strength of cockle shell concrete is comparable with plain concrete.